Treatment of two Garlic Cultivars Allium sativum L. for Spraying with Amino Acid Ornithine and Organic Extracts as Tea Fertilizer in Vegetative Growth Traits - Muhannad Mahmoud Al-Muhairi; Thamar Al-Ajili (مجلة جامعة كركوك للعلوم الزراعية)
The experiment was conducted at the research station of the Department of Horticulture and Landscape Engineering- College of Agriculture-Tikrit University, during the 2019-2020 growing season to study the effect of garlic cultivars and spraying with the amino acid ornithine at different concentrations (0, 50, 100, 150) mg L-1 and spraying with organic extract fertilizer tea Compost with three concentrations (0, 5, 10)% in the characteristics of vegetative growth in garlic for the two types of garlic plants are: the first (domestic) variety, and the second (foreign) variety, showing the possibility of planting it and improving the nutritional value and benefiting from the components of vegetative growth as an economic crop in Salah al-Din Governorate, and the factorial process was carried out according to the design of the Complete Diversified Sectors (RCBD), a factorial experiment in splintered cuts”, with three replicates, each replicate 24 experimental units, and each experimental unit 20 plants, and the three factors of the experiment were as follows:Varieties: The local variety was significantly superior to the foreign variety in terms of plant height of 81.48 cm-1, leaf area of 93.41 cm2 plant-1 , length reaching 44.81 cm plant-1 , and leaf mound of chlorophyll total amounted to 51.85 ASPD, respectively. Histidine: The concentration of the amino acid ornithine (150) mg L-1 achieved the best results significantly in the characteristic of plant height 84.95 cm plant-1, leaf area reached 107.24 cm plant-1, length reached 47.22 cm plant-1 , and total chlorophyll granule 58.36 ASPD Straight. The first focus is t1 (no addition), the third focus is t2 (5) and the third focus is t3 (10). The third concentration (10)% was significant in the character of plant height was 88.24 cm plant-1, leaf area was 103.34 cm2 plant-1, and height was 48.64 cm plant-1 and chlorophyll was 55.78 ASPD.Triple interaction between cultivars and the amino acid ornithine and organic extract:The concentration achieved (150) mg L-1 and a level (10) % significantly in the characteristics of plant height reached 93.98 cm-1 and leaf area reached 129.16 cm 2 plant-1 and height reached 52.81 cm plant-1 and total chlorophyll content reached 15.50 ASPD respectively . The interaction of the local cultivar with concentration (150) mg L-1 and concentration (5) % was significantly superior in the traits of height that reached 48.08 cm plant-1 and leaf area reached 114.33 cm 2 plant-1 and the total chlorophyll was 63.20 ASPD. While the concentration (150) mg L-1 and the level (5) % in leaf area traits were 97.96 cm2 plants-1, respectively. Whilethe foreign cultivar with a concentration of (100) mg per liter -1 and a concentration of (10) % exceeded in the number of leaves, it was 13.36 leaves-1, respectively.